Diethylamine: a smart organocatalyst in eco-safe and diastereoselective synthesis of medicinally privileged 2-amino-4H-chromenes at ambient temperature - Kulkarni, Makarand A.; Pandit, Kapil S.; Desai, Uday V.; Lad, Uday P.; Wadgaonkar, Prakash P. (Comptes Rendus Chimie, 2013)
Diethylamine has been demonstrated to be an efficient organocatalyst in the diastereoselective synthesis of Bcl-2 protein antagonist (HA-14-1) and of its structural analogues by one-pot condensation between salicylaldehyde and three different C-H acids, viz, ethyl cyanoacetate, phenylsulfonyl acetonitrile, and malononitrile. Easy commercial availability of the catalyst at extremely low cost and avoidance of conventional work-up as well as purification procedures qualifies this scalable protocol for a ``near-ideal synthesis''. (c) 2013 Academie des sciences. Published by Elsevier Masson SAS. All rights reserved.
Keywords: 2-amino-4H-chromenes; Active methylene compounds (C-H acids); diethylamine; multicomponent reactions; organocatalyst

Diethylamine-catalyzed environmentally benign synthesis of 1-oxo-hexahydroxanthenes and bis-coumarins at ambient temperature - Kupwade, Ravindra V.; Pandit, Kapil S.; Desai, Uday V.; Kulkarni, Makarand A.; Wadgaonkar, Prakash P. (Research on Chemical Intermediates, 2016)
An extremely simple, economical and environmentally benign protocol has been described for one-pot synthesis of 1-oxo-hexahydroxanthenes by pseudo three-component condensation between salicylaldehydes and dimedone, cyclohexane-1,3dione or 5-methyl cyclohexane-1,3-dione using diethylamine as the catalyst. Based upon the mechanism of the reaction, the protocol has been extended towards the synthesis of tetraketones and bis-coumarins.

Diethylamine Dess-Martin periodinane: an efficient catalyst-oxidant combination in a sequential, one-pot synthesis of difficult to access 2-amino-3,5-dicarbonitrile-6-sulfanylpyridines at ambient temperature - Kupwade, Ravindra V.; Khot, Supriya; Kulkarni, M. A.; Desai, Uday V.; Wadgaonkar, Prakash P. (RSC Advances, 2017)
Herein, diethylamine Dess–Martin periodinane has been demonstrated for the first time as an efficient catalyst–oxidant combination in a sequential, one-pot synthesis of medicinally privileged but difficult to access 2-amino-3,5-dicarbonitrile-6-sulfanylpyridines via a pseudo-four component reaction between 2,6-disubstituted benzaldehydes, malononitrile, and thiols. Ambient reaction conditions, excellent yields, and total avoidance of conventional isolation as well as purification are the noteworthy merits of this developed protocol.

Design, synthesis, and gas permeation properties of polyimides containing pendent imidazolium groups - Shrimant, Bharat; Kharul, Ulhas K.; Wadgaonkar, Prakash P. (Journal of Polymer Science Part A-Polymer Chemistry, 2018)
Film-forming polymers containing ionic groups have attracted considerable attention as emerging materials for gas separation applications. The aim of this article was to synthesize new film-forming polyimides containing imidazolium groups (PI-IMs) and establish their structure-performance relationship. In this context, a new aromatic diamine, namely, N-1-(4-aminophenyl)-N-1-(4-(2-phenyl-1H-imidazol-1-yl)phenyl)benzene-1,4-diamine (ImTPADA), was synthesized and polycondensed with three aromatic dianhydrides, namely, 4,4-(hexafluoroisopropylidene)diphthalic anhydride, 4,4-(4,4-isopropylidenediphenoxy) bis(phthalic anhydride), and 4,4-oxydiphthalic anhydride to form the corresponding polyimides containing pendent 2-phenylimidazole groups (PI-IEs). Next, PI-IMs were prepared by N-quaternization of pendent 2-phenylimidazole groups present in PI-6FDA using methyl iodide followed by anion exchange with bis(trifluoromethane)sulfonimide lithium salt (LiTf2N). PI-IEs and PI-IMs exhibited reasonably high molecular weights, amorphous nature, good solubility, and could be cast into self-standing films from their DMAc solutions. Thermogravimetric analysis showed that 10% weight loss temperature of PI-IEs and PI-IMs were in the range 545-475 degrees C and 303-306 degrees C, respectively. Gas permeability analysis of films of PI-IEs and PI-IMs was investigated by variable-volume method and it was observed that incorporation of ionic groups into PI-6FDA resulted in increased permeability while maintaining selectivity. In particular, polymer bearing Tf2N- anion exhibited high CO2 permeability (33.3 Barr) and high selectivity for CO2/CH4 (41.1) and CO2/N-2 (35.4). (c) 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2018, 56, 1721-1729

Design and synthesis of aromatic polyesters bearing pendant clickable maleimide groups - Nagane, Samadhan S.; Kuhire, Sachin S.; Jadhav, Uday A.; Dhanmane, Sushilkumar A.; Wadgaonkar, Prakash P. (Journal of Polymer Science Part A-Polymer Chemistry, 2019)
A bisphenol bearing pendant maleimide group, namely, N-maleimidoethyl-3, 3-bis(4-hydroxyphenyl)-1-isobenzopyrrolidone (PPH-MA) was synthesized starting from phenolphthalein. Aromatic (co)polyesters bearing pendant maleimide groups were synthesized from PPH-MA and aromatic diacid chlorides, namely, isophthaloyl chloride (IPC), terephthaloyl chloride (TPC), and 50:50 mol % mixture of IPC and TPC by low temperature solution polycondensation technique. Copolyesters were also synthesized by polycondensation of different molar proportions of PPH-MA and bisphenol A with IPC. Inherent viscosities and number-average molecular weights of aromatic (co)polyesters were in the range of 0.52-0.97 dL/g and 20,200-32,800 g/mol, respectively indicating formation of medium to reasonably high-molecular-weight polymers. C-13 NMR spectral analysis of copolyesters revealed the formation of random copolymers. The 10% weight loss temperature of (co)polyesters was found in the range 470-484 degrees C, indicating their good thermal stability. A selected aromatic polyester bearing pendant maleimide groups was chemically modified via thiol-maleimide Michael addition reaction with two representative thiol compounds, namely, 4-chlorothiophenol and 1-adamantanethiol to yield post-modified polymers in a quantitative manner. Additionally, it was demonstrated that polyester containing pendant maleimide groups could be used to form insoluble crosslinked gel in the presence of a multifunctional thiol crosslinker. (c) 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2019, 57, 630-640
Keywords: crosslinking; maleimide group; modification; polyesters; thiol-maleimide

Development of reversed-phase HPLC method for purity assessment of aryl porphyrins and their metal complexes - Ujagare, Ashish Mohan; Uzagare, Matthew C.; Ghogare, Bhausaheb N.; Gupta, Lokesh Kumar; Wadgaonkar, Prakash P.; Patil, Vishwanath R.; Donde, Kamini J. (SSC Plus, 2025)
A gradient reversed-phase HPLC method was developed for in-process monitoring of the formation of aryl porphyrins and their corresponding metallo-aryl porphyrins. The method also proved effective for determining their quantitative purity. Optimal results achieving proper peak shape and separation of peaks in the chromatogram were obtained using C8 column and gradient of acetic acid-water and acetonitrile. The detector wavelength was selected for simultaneous detection of starting materials and products for in-process analysis for conversion of aryl aldehydes to corresponding tetraaryl porphyrins at 254 nm and metallo-aryl porphyrins formation from tetraaryl porphyrin at 413 nm, respectively; while the purity of products could be determined at 413 nm. The developed method is efficient, versatile, accurate, and easy to carry out and could serve as a handy tool for the reaction monitoring and determination of purity in the processes development of synthetic porphyrins and metalloporphyrins.